Can “LITE” Procedure Combined With a Short Course Antibiotic Treatment Be Effective in Treating the Chronic PJI?—A Prospective Randomized Controlled Trial - Yang Chen; Haiqi Ding; Qijin Wang; Zida Huang; Chaofan Zhang; Wenbo Li; Yansheng Lin; Yufeng Guo; Xinyu Fang; Wenming Zhang (Orthopaedic Surgery)
ABSTRACT Objective The prevailing treatment for chronic periprosthetic joint infection (PJI) is a two‐stage exchange, yet the optimal duration of antibiotic therapy following this procedure remains a topic of debate. This study aimed to determine whether a short course of postoperative antibiotic therapy can maintain infection control rates following a long interval two‐stage exchange (LITE) for PJI. Methods We conducted a prospective study enrolling patients with chronic PJI who underwent the LITE procedure at our institution from April 2018 to November 2021. Patients were randomly assigned to receive either a long course (12 weeks) or short course (2 weeks) of postoperative antibiotics. The pathogens, antibiotics, inflammatory markers, antibiotic‐related complications, cases of reinfection, or re‐operation were recorded. Continuous variables were analyzed using the two‐sample t‐test or Mann–Whitney U test, and categorical variables were analyzed using Fisher's exact tests. Kaplan–Meier survival analysis was used to compare infection control rates. Results A total of 60 patients with chronic PJI who completed the LITE procedure were included in the study (30 patients per group). All patients were followed for a minimum of 24 months (mean 39.2 ± 13.0 months). We observed that the infection control rate in the short‐course group was not inferior to that in the long‐course group (96.7% vs. 96.7%, p = 1.000). Conclusions For patients with chronic PJI undergoing the LITE procedure, a 2‐week course of postoperative antibiotics suffices to maintain infection control rates. Trial Registration Chinese Clinical Trial Registry: ChiCTR1900027089